Endovascular thrombectomy for acute ischaemic stroke: a real‐world experience. Issue 9 (16th September 2016) - Cappelen‐Smith, C.; Cordato, D.; Calic, Z.; Cheung, A.; Wenderoth, J.
Abstract : Background: Endovascular thrombectomy for acute ischaemic stroke due to proximal vessel occlusions in the anterior cerebral circulation within 6 h of stroke onset is now recognised as highly beneficial. Five randomised controlled trials in 2015 showed significant improvement in functional outcome at 90 days compared with intravenous thrombolysis alone. Liverpool Hospital is a tertiary referral centre with an acute stroke service, including 24/7 intravenous thrombolysis and endovascular thrombectomy. Aim: To determine whether good functional outcomes with endovascular thrombectomy are achievable in patients with acute ischaemic stroke under 'real‐world conditions' at an Australian tertiary referral centre. Methods: A retrospective analysis of functional outcomes and mortality of 33 consecutive patients undergoing endovascular thrombectomy for acute ischaemic stroke in the anterior circulation at Liverpool Hospital over 24 months (2014–2015), including 13 'drip and ship' patients transferred from other centres. Results: Functional outcomes defined as 90‐day modified Rankin scale (mRS) were similar to published trials with a good outcome noted in 39.4% (mRS 0–2) of patients. Lower admission National Institutes of Health Stroke Scale score and shorter time to recanalisation from stroke onset correlated with good outcome ( P < 0.05). Outcomes were not statistically different between the local and transferred cases. Mortality was not higher than historical rates for anterior circulation strokes due to proximal vessel lesions. Conclusions: This cohort of patients with anterior cerebral circulation occlusions was treated outside the well‐resourced situation of clinical trials and good functional outcomes are similar. The study translates endovascular thrombectomy to a 'real‐world' situation.